JOKOWI DI DEPAN DAN BELAKANG PANGGUNG POLITIK - Leovina Prinanda Putri; Muhammad Ahsan Ridhoi; Novita Anggraini (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2021)
Indonesia reached a turning point in its implementation of eradicating corruption after the fall of the Soeharto regime in 1998. Corruption then became a sexy issue that became the commitment of politicians and public officials. Jokowi appeared and became a favorite media. In the 2014 presidential election campaign, Jokowi carried 9 Nawa Cita promises, on the 4th point containing: "rejecting weak countries by reforming the system and law enforcement that is free of corruption, with dignity, and trustworthy". Eradication of corruption in Indonesia has not been fully effective. This shows commitment to eradicating corruption and strengthening the KPK through words like what Jokowi did, only dramaturgy to deal with communication and self-image crises. Jokowi does not want to present himself as supporting the revision of the KPK Law. Jokowi seems to be with the people, united to support the strengthening of the KPK. By collecting qualitative data related to a collection of statements by President Jokowi about strengthening the KPK in a number of mass media in the 2014-2021 period, the researcher uses the Front Stage and Back Stage theories by Erving Goffman. This study explains how Jokowi uses him as head of state and also as part of the people based on the best version of himself.